Countering violent extremism: making gender matter - Pearson, Elizabeth (Rethinking political violence, 2020)
This book presents original research on gender and the power dynamics of diverse forms of violent extremism, and efforts to counter them. Based on focus group and interview research with some 250 participants in Canada, France, Germany, the Netherlands and UK in 2015 and 2016, it offers insights from communities affected by radicalisation and violent extremism. It introduces the concept of gendered radicalisation, exploring how the multiple factors of paths to violent extremist groups - social, local, individual and global - can differ for both men and women, and why. The book also offers a critical analysis of gender and terrorism; a summary of current policy in the five countries of study and some of the core gendered assumptions prevalent in interventions to prevent violent extremism; a comparison of Jihadi extremism and the far right; and a chapter of recommendations. This book is of use to academics, policy-makers, students and the general reader interested in better understanding a phenomenon defining our times.